Drug-Excipients Compatibility Studies of Molnupiravir in an Attempt of Developing a Stable Molnupiravir Capsule Formulation for the Treatment of COVID-19 - Agarwal, Sumit; Sidhan, Rajasekaran (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Molnupiravir is an antiviral medication primarily used for the treatment of COVID-19. Clinical trials have shown that molnupiravir reduces the risk of hospitalization and death due to COVID- 19 when taken early in the course of infection. The USFDA had granted an EUA (emergency use authorization) in December 2021 for molnupiravir to treat COVID-19. Many other countries have also authorized its use under emergency provisions. The current research focuses on performing Drug-Excipients Compatibility Studies of Molnupiravir in an attempt of developing a Stable Molnupiravir Capsule formulation-200 mg. Materials and Methods: Compatibility of various excipients with Molnupiravir API was studied. Drug and individual excipients were mixed in 1:1 ratio and filled in USP Type I transparent glass vials. Samples were tested at initial, 15 days, 30 days for Description, Assay and Related substances. Appropriate excipients were chosen based on the results obtained. With the selected excipients 3 different capsule formulations were prepared by varying the excipients quantities and were studied for Assay, Related Substances and Dissolution profile for determining the best suitable formula. Results: Among three different formulations manufactured, The Assay, Related Substances and Dissolution profile of Formulation 3 was found satisfactory. Conclusion: Formulation 3 was found to be the best suitable formula and was considered for formulating Molnupiravir 200 mg Capsules and for further studies.
Keywords: Antiviral; COVID-19; Drug-Excipients Compatibility Studies; Emergency Use; Authorization; Molnupiravir